Radiological impact assessment in the terrestrial environment of Greece using innovative tools – Adaptation of ERICA Tool to actual measurements - Sotiropoulou, M.; Florou, H.; Kitis, G. (HNPS Advances in Nuclear Physics, 2019)
In the present study, the radioactivity levels in terrestrial non-human biota and the transfer pathways in the ecosystem are examined. Grass of Poaceae family and herbivore mammals (ruminants) of Bovidae family and soil samples were collected during the period of 2010 to 2014, from grasslands of the Greek rural territory where sheep and goats were free-range grazing. Natural background radionuclides (226Ra, 228Ra, 228Th) and artificial radionuclides (137Cs, 134Cs, 131I) were detected in the collected samples using gamma spectrometry. The actual measured activity concentrations and site- specific data of the studied organisms were imported in ERICA Assessment Tool (Version 1.2.1, February 2016) in order to provide an insight of the radiological dose rates. Natural radionuclides exhibited significantly higher contribution to the total dose rate than the artificial ones. The radiological exposure to Fukushima-derived radionuclides was quite low and owed to internal exposure, mainly derived through the ingestion pathway. According to the screening levels, the calculated dose rate to the studied non-human biota was below the threshold levels. However, the obtained results may be proved useful in further research regarding the possible impact of protracted low level ionising radiation to non-human biota on the various levels of life’s organization.